Economic failure and the role of plant age and size: First evidence from German administrative data - Steffen Müller; Jens Stegmaier (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
This paper introduces a large-scale administrative panel data set on corporate bankruptcy in Germany that allows for an econometric analysis of involuntary exits where previous studies mixed voluntary and involuntary exits. Approximately 83 percent of all bankruptcies occur in plants with no more than 10 employees, and 61 percent of all bankrupt plants are not older than 5 years. The descriptive statistics and regression analysis indicate substantial negative age dependence with respect to bankruptcy risk but confirm negative size dependence for mature plants, only. Our results corroborate hypotheses stressing increasing capabilities and positional advantage, both predicting negative age dependence with respect to bankruptcy risk due to productivity improvements. The results are not consistent with the theories explaining age dependence via imprinting or structural inertia. – – Dieses Papier stellt einen neuartigen Panel-Datensatz zu Insolvenzen für Deutschland vor, der es im Gegensatz zu anderen Studien erlaubt, ökonometrische Analysen zu unfreiwilligen Schließungen durchzuführen. Wir finden, dass ca. 83 Prozent aller Insolvenzen in Betrieben mit weniger als 10 Beschäftigten stattfinden und 61 Prozent aller insolventen Betriebe nicht älter als 5 Jahre sind. Unsere Deskriptionen und Regressionen verweisen darauf, dass das Insolvenzrisiko mit dem Betriebsalter geringer wird. Ein negativer Zusammenhang zwischen Betriebsgröße und Insolvenzrisiko lässt sich jedoch nur für ältere Betriebe nachweisen. Unsere Ergebnisse unterstützen Hypothesen, die von Produktivitätsvorteilen älterer Betriebe ausgehen. Sie sind nicht kompatibel mit Hypothesen, die mit dem Alter steigende Risiken erwarten, z.B. aufgrund überholter oder verkrustender betrieblicher Strukturen.
Keywords: L1; L2; 330; bankruptcy; plant exit; organizational mortality